The French Consul Chevalier Laurent d'Arvieux and his plan to invade Algeria in 1675 - saadi, Khemissi (The Algerian Historical Journal, 2026)
European countries have been waiting for opportunities to seize and invade North African regions since Spain succeeded in The Reconquista, and despite the diplomatic relations that linked the Ottoman country with those countries, the consuls and ambassadors of those countries did not stop preparing reports and sending memorandums about the political situation in North Africa. And about its military power in preparation for its invasion, including a memorandum from the French Consul (Chevalier d'Arvieux Laurent) to invade Algeria and presented it to the Prince of Portugal. Through this article, we aim to introduce it and its details, to conclude that the intention of aggression was premeditated if the opportunity allowed, and this project is an example of dozens of projects. This indicates that the idea is circulating among official bodies and the diplomatic corps.